PENGARUH LAMA FERMENTASI TAPAI PISANG TANDUK (Musa corniculata J. De Leureiro) SEBAGAI RANCANGAN LEMBAR KERJA SISWA (LKS) PADA PEMBELAJARAN BIOLOGI - Astati, Rita; Mahadi, Imam; ', Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The purpose of this research is to know the influence of fermentation time toward the result of fermented of pisang tanduk (Musa corniculara J. De Leureiro) this research was conducted in December 2016. The result of this research is used for LKS design on conventional biotechnology concept of class XII Senior High School. This research was conducted with 2 phases; those are the stage of making fermented of pisang tanduk by using experiment research and planning phase of LKS. The experimental research was conducted by using Completely Randomized Design (RAL) which consisted of 6 treatments and 3 replications so that 18 experimental designs were obtained. If there are any differences between treatments then continued test Duncan Multiple Range Test (DMRT) at 5% level. Parameters observed included alcohol (%), moisture (%), pH and organoleptic levels (color, flavor, texture, and taste). The results showed that fermentation time had significant effect on alcohol content, moisture content, pH, and organoleptic (color, flavor, texture, and taste) the fermented of pisang tanduk (Musa corniculata J. De Leureiro). The best time of fermentation is 42 hours with average alcohol content 0,77%, moisture content 51,27%, pH 3,29 and produces organoleptik favored by panelist. The result of this research has potential as LKS design on conventional biotechnology concept in Biology class XII high school.Keyword : Fermented of pisang tanduk, Fermentation time, Student Worksheet (LKS)